(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To compare the effectiveness and tolerability of misoprostol as a cervical ripening agent in first trimester abortion through sublingual and vaginal routes of administration. Material and Methods: This study was carried out in the department of Obst. & Gynae Teerthanker Mahaveer Medical College and Research Centre (TMMC&RC). A total of 120 patients were included in the study. They were divided in two groups Group A 60 patients sublingual Group B 60 patients vaginal The drug was administered 3-4 hours before suction and evacuation by sublingual and vaginal routes. Efficacy was assessed on the basis of time taken for ripening, dilatation achieved, duration of the procedure, intraoperative blood loss and pain. The patients tolerability was noted on the basis of side effects. Results: The mean time taken for cervical ripening was more in the sublingual group as compared to the vaginal ( P<0.001).The duration of suction and evacuation was less as compared to the vaginal route. The mean intraoperative blood loss was more in sublingual as compared to the vaginal group. The intraoperative pain score was comparatively lower (P<0.05) as compared to the vaginal route. Side effects like loose motions, nausea vomiting were more with sublingual group. Conclusion: Sublingual Misoprostol is an effective and favourable cervical ripening agent for 1st trimester abortions. Bangladesh J Obstet Gynaecol, 2012; Vol. 27(2) : 63-66